Assessment of Ichthyo-Fauna and Certain Biodiversity Indices in Jaisamand Lake, India - V.K. Balai; L.L.Sharma; N.C.Ujjania (Journal of Indian Fisheries Association, 2020)
The ichthyo-fauna diversity of Jaisamand Lake, India is described in the present paper based on a study conducted during 2005-06. A total 40 fish species under 7 orders and 13 families were recorded from this lake. Observed fish fauna was dominated by family Cyprinidae representing 19 species followed by Bagaridae 4 species, Channidae 3 species, Mastacembelidae, Siluridae, Cobitidae, Ambassidae 2 species each, while Balitoridae, Heteropneustidae, Belonidae, Cichlidae, Notopteridae and Gobiidae with 1 species each. The Shannon-Weiner Diversity Index (0.838), Simpson's index (0.745) and Pielous species evenness Index (0.044-0.838) were also Calculated. Comparatively low values of these indices indicate the variability and change in the fish diversity that may be attributed to the changes in the aquatic environment and unprecedented dominance of exotic fish tilapia.